Accounting for Multiple Nonfatal Strangulation in Intimate Partner Violence Risk Assessment. Issue 11 (June 2022) - Messing, Jill Theresa; Campbell, Jacquelyn; AbiNader, Millan Alexander; Bolyard, Richelle
Nonfatal strangulation is a prevalent, underreported, and dangerous form of intimate partner violence (IPV). It is particularly important to assess for strangulation among abused women as this form of violence may not leave visible injury. The most severe negative physical and mental health consequences of strangulation appear to be dose-related, with those strangled multiple times or to the point of altered consciousness at higher risk of negative sequelae. This research examines the relationship between multiple strangulation, loss of consciousness due to strangulation, and risk of future near-fatal violence to modify the Danger Assessment (DA) and the Danger Assessment for Immigrant women (DA-I), IPV risk assessments intended to predict near-fatal and fatal violence in intimate relationships. Data from one study ( n = 619) were used to modify the DA to include an item on multiple strangulation or loss of consciousness due to strangulation. Data from an independent validation sample ( n = 389) were then used to examine the predictive validity of the updated DA and DA-I. The updated version of the DA predicts near-fatal violence at 7–8 months follow-up significantly better than the original DA. Adding multiple strangulation or loss of consciousness to the DA-I increased the predictive validity slightly, but not significantly. The DA and DA-I are intended to be used as a collaboration between IPV survivors and advocates as tools for education and intervention. Whether or not an IPV survivor has been strangled, she should be educated about the dangerous nature of strangulation and the need for medical intervention should her partner use strangulation against her. This evidence-based adaptation of the DA and DA-I may assist practitioners to assess for and intervene in dangerous IPV cases.